2019
DOI: 10.1186/s12978-019-0815-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexually transmitted infections and associated factors among the University of Gondar students, Northwest Ethiopia: a cross-sectional study

Abstract: IntroductionGlobally, sexually transmitted infections (STIs) remain a major public health problem. University students tend to practices sex which predisposes them to sexually transmitted infections, unwanted pregnancies, and unsafe abortions due to their freedom from families. Therefore, the study aimed to assess the prevalence of sexually transmitted infections and associated factors among the University of Gondar students, northwest Ethiopia.MethodsAn institution based cross-sectional study was conducted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
3
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 14 publications
8
47
3
6
Order By: Relevance
“…In the present study, 17.3% had ever watched pornography. This is lower than the gure reported for students of University of Gondar (55.5%), Bahir Dar University (65.4%) and Debre Berhan University (52.6%) [22,23,38]. In line with these two studies, we also found that watching pornography was common among males than females, suggesting that male students are more interested in sex than female students.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In the present study, 17.3% had ever watched pornography. This is lower than the gure reported for students of University of Gondar (55.5%), Bahir Dar University (65.4%) and Debre Berhan University (52.6%) [22,23,38]. In line with these two studies, we also found that watching pornography was common among males than females, suggesting that male students are more interested in sex than female students.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study 34.1% of study participants reported to have two or more sexual partners which is less than that of students of Aksum University (64.4%), University of Gondar (54.2%), private colleges in Bahir Dar (45.3%) and Bahir Dar University (42.7%) [23,29,36,38] but greater than that of students of private colleges in Mekelle (30.5%), Mizan Aman College of Health Sciences (16.3%) [37], and Madawalabu, Wollega, Debre Berhan and Jigjiga universities, and governmental higher institution in Debre Markos, in which33.6%, 31.3%,21.4%, 33.2% and 30.14%had multiple sexual partners,respectively [22,24,25,31,33,41].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…7 Sexually transmitted infections including HIV/AIDS are high among students having poor knowledge. 8 University students are at higher risk of engaging in risky sexual behavior, especially if they are under the influence of alcohol or drugs and lack the necessary maturity in handling negative peer pressure. 9 Level of personal knowledge is considered essential for acquiring optimum health, in which, in this context, HIV/ AIDS knowledge represents the acquisition of scientific facts and information regarding the symptoms, way of transmission, adverse consequences, and prevention strategies of the disease.…”
Section: Introductionmentioning
confidence: 99%